Developing The Creativity of Pencak Silat: A Systematic Literature Review - Deny Pradana Saputro; Nasuka Nasuka; M.E. Winarno; Sulaiman Sulaiman (International Conference on Science, Education, and Technology, 2023)
Creativity is a very important element for students of pencak silat to have. This is because creativity contributes to helping a person achieve his desires. Given the importance of creativity which is needed in almost all aspects, this needs to be achieved through self-development. Based on this, this study aims to find out how to develop creativity in pencak silat. The method used in this study is a systematic literature review. Search range for articles in 2018-2023. The keywords used are "Pencak silat" OR "Martial art" OR "Martial arts" AND "creativity". The results of the literature review show that currently, the method that can be used to develop the creativity of pencak silat students is the alphabet method. This method is very important because it can shape the creativity of pencak silat students. Currently, the alphabet method is the only method found in this literature study. Therefore, these findings can also be used as a reference for developing other creativity development methods to increase the creativity of pencak silat students.